Empathy with Nature and an Autistic Spirituality - Nygren, Anna (Journal of Ecohumanism, 2023)
Anna Stenning does in the anthology Neurodiversity. A New Critical Paradigm (2020) introduce an autistic ethics using the autobiographies of Greta Thunberg (No One Is Too Small to Make a Difference (2019)) and Temple Grandin (Animals in Translation (2005)). Stenning points to how this autistic ethics do expand its acts of care to the more-than-human. Grandin describes her being in the world as more attuned to animals than humans. Thunberg argues that her Asperger’s is the reason why she can care so totally for the climate. This article further investigates the intersection of autism and the more-than-human, or the post humanist. Using the works of openly autistic authors Madeleine Ryan (A Room Called Earth (2020)) and Hannah Emerson (You Are Helping This Great Universe Explode (2020)) as well as Emily Dickinson, posthumously diagnosed with autism. I investigate the autistic theme of nature and the autistic relationship to other species. This relation often seems to be stronger and more genuine than the relation to other humans. I propose that the autistic sense of the more-than-human is at once a response to the oppressive view of the autistic as less-than-human – a way of finding one’s allies outside the realms of human civilization – and a special kind of autistic worldly spiritualness that includes an ethics that do not segregate one life form from another.